Therapeutic plasma exchange for thrombotic thrombocytopenic purpura with refractory thrombocytopenia. Issue 3 (22nd December 2017) - Maloney, Nolan; Martin, Isabella; Szczepiorkowski, Zbigniew M.; Dunbar, Nancy M.
Abstract : Thrombotic thrombocytopenic purpura (TTP) is an acute, life‐threatening illness with disseminated platelet‐rich thromboses of small vessels that variably presents with the classic clinical "pentad" of microangiopathic hemolytic anemia, thrombocytopenia, fever, altered mental status, and acute kidney injury. Most cases are caused by an acquired autoantibody to ADAMTS13, a metalloproteinase that cleaves large von Willebrand Factor (vWF) multimers. The mainstay of treatment is daily therapeutic plasma exchange (TPE), sometimes with adjunctive pharmacologic immunosuppression. TPE is generally continued until the platelet count is greater than 150 × 10 3 /µL and the lactate dehydrogenase is near normal for 2‐3 consecutive days. Unfortunately, there is no clear guidance for when thrombocytopenia is refractory for a prolonged period of time. The following case describes such a scenario in which consecutive ADAMTS13 activity and inhibitor levels were used to guide the decision to stop treatment with TPE in a patient who failed to recover their platelet count.